Regulasi Penyiaran Digital: Dinamika Peran Negara, Peran Swasta, dan Manfaat bagi Rakyat - Ervan Ismail; Siti Dewi Sri Ratna Sari; Yuni Tresnawati (Jurnal Komunikasi Pembangunan, 2019)
Digitalization must begin a strong law that is Acts. Based on the records, digital broadcasting regulations using Republic of Indonesia Minister of Communication and Informatics’s regulations could be canceled through lawsuits at Supreme Court and State Administration Court. Broadcast digitalization was begun in 2011 through a digitalization Road Map and till date, the process at House of Representatives has not been completed. 85% of countries in the world have migrated to digital broadcasts. The study aims to describe how changes and various roles in broadcasting digitalization if the revision of the Broadcasting Acts is implemented. The study also aims to find out the impact and benefits of broadcasting digitalization for the public and broadcasting stakeholders compared to present Broadcasting Acts. This study uses participant observation methods and text analysis to categorize the articles of digitalization in the revision draft of the Broadcasting Acts from the House of Representatives Commission I in 2017, accompanied by media coverage analysis. Discourse analysis is used to relate to the problems arised due to broadcast digitalization. The results show that digitalization can provide more channels in the same space than analog broadcasting. Political parties and state institutions will be allowed to have broadcasting institutions. The State through Television Radio of the Republic of Indonesia (RTRI) will become the important player in terrestrial digital broadcasting with a single multiplexer (mux) system, which is considered undemocratic for private television associations. All "television stations" will change and compete to become "content providers" similar to new digital televisions. The government will formulate the mechanisms, socialization, models, roles in digitalizing television broadcasting in a blue print. Digital dividend will be used for the development of internet and telecommunications. The dynamics that occur due to interests’ differences of the state, the private sector and society take part at each stage of broadcasting digitalization regulation. The conclusion of the study illustrates that the use of digital technology in broadcasting through the Acts’ revision could be a solution for both frequency limitation and the efficient use for more diverse broadcasters (diversity of ownership).